2014
DOI: 10.1002/cbic.201402541
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Structure–Function Correlations of Bacillus subtilis Acetolactate Synthase

Abstract: Isobutanol is deemed to be a next-generation biofuel and a renewable platform chemical.1 Non-natural biosynthetic pathways for isobutanol production have been implemented in cell-based and in vitro systems with Bacillus subtilis acetolactate synthase (AlsS) as key biocatalyst.2-6 AlsS catalyzes the condensation of two pyruvate molecules to acetolactate with thiamine diphosphate and Mg(2+) as cofactors. AlsS also catalyzes the conversion of 2-ketoisovalerate into isobutyraldehyde, the immediate precursor of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…As a synthetase with great economic value, cALS has been optimized for its stability. As reported so far, several key residues of cALS of B. subtilis were mutated, which confirmed that the mutant Q424S had significantly improved thermo-stability and catalytic efficiency that was almost unchanged; by contrast, the efficiency of enzymatic activity of Q487S improved, and thermostability decreased significantly (Sommer et al, 2015). However, there are few reports about mutations of cALS to optimize acid tolerance, so our study provides a baseline for mutations that code for acid tolerance in cALS.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As a synthetase with great economic value, cALS has been optimized for its stability. As reported so far, several key residues of cALS of B. subtilis were mutated, which confirmed that the mutant Q424S had significantly improved thermo-stability and catalytic efficiency that was almost unchanged; by contrast, the efficiency of enzymatic activity of Q487S improved, and thermostability decreased significantly (Sommer et al, 2015). However, there are few reports about mutations of cALS to optimize acid tolerance, so our study provides a baseline for mutations that code for acid tolerance in cALS.…”
Section: Discussionsupporting
confidence: 84%
“…These relatively ideal scores indicated the models had correct fold and the correct topology, which ensured the rationality of the predicted model. By aligning to the known structures of cALS from other species (B. subtilis, PDB ID: 4RJJ; Arabidopsis thaliana, PDB ID: 1Z8N; K. pneumoniae, PDB ID: 1OZG; Saccharomyces cerevisiae, PDB ID: 1T9B) (Pang et al, 2004;McCourt et al, 2005;McCourt et al, 2006;Sommer et al, 2015), our results showed that BlALS was significantly conserved in the predicted active center: (i) the K38 and Q485 of BlALS participated in the catalytic mechanism, as confirmed in cALS from K. pneumonia (Pang et al, 2004); (ii) the Q122, Q422, M481, and Y490 of BlALS was important to the accurate localization of ThDP to promote the generation of the second condensation reaction of acetyl-lactic acid, as confirmed in cALS from B. subtilis (Sommer et al, 2015). These residues were conservative in sequence and conformation ( Figure 3D), which further verified the reliability of the predicted model.…”
Section: Modeling and Site-directed Mutagenesis Of Blalsmentioning
confidence: 99%
“…We chose the AlsS from B. subtilis to stabilize because it has a known crystal structure 31 and unlike many other family members 32 , it is FAD independent and the oligomer is constructed from a single polypeptide chain. To stabilize AlsS from B. subtilis , we employed the PROSS stabilization design server 33 keeping the subunit interface residues fixed (using PDB Code: 4RJK), again speculating that increased thermostability might also increase solvent stability.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). ALS was also reported to play a distinct role in sodium-ion homeostasis in plant cells, plant patterning and development [ 49 ] as well as isobutanol biosynthesis [ 50 ], important for bacteria resistance to environmental stress [ 51 ]. Consequently, we speculate that ALS III is a crucial enzyme in metabolic pathway controlling R. palustris PSB-S adaption to pyrazosulfuron-ethyl stress.…”
Section: Discussionmentioning
confidence: 99%